Analysis of Organizing Functions to Improve The Delivery Time of Apbdes Reports at The Community and Village Empowerment Office of Gunungsitoli City - Lase, Apryantho; Lahagu, Palindungan; Hulu, Fatolosa; Zega, Yamolala (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
This study aims to analyze the role of organizing functions in improving the timeliness of Village Revenue and Expenditure Budget (APBDes) report submission at the Community and Village Empowerment Office (PMD) of Gunungsitoli City. A descriptive qualitative method was employed, using in-depth interviews with five key informants, consisting of structural officials and technical staff in village administration and finance. The findings reveal that the organizing function covering task division, delegation of authority, coordination, and supervision has not been effectively implemented. Work overload, centralized delegation of authority, weak interdepartmental coordination, and lack of strict sanctions in supervision contribute to delays in report submission. Internal organizational challenges and limited village capacity further exacerbate these issues. Improvement strategies include digitalization, technical training, and workflow restructuring, though their implementation remains partial. This research highlights the importance of optimizing organizing functions to enhance timeliness in administrative reporting. The study provides practical insights for strengthening public organizational management and village financial accountability.